2021
DOI: 10.1371/journal.pgen.1009312
|View full text |Cite
|
Sign up to set email alerts
|

Vestigial mediates the effect of insulin signaling pathway on wing-morph switching in planthoppers

Abstract: Wing polymorphism is an evolutionary feature found in a wide variety of insects, which offers a model system for studying the evolutionary significance of dispersal. In the wing-dimorphic planthopper Nilaparvata lugens, the insulin/insulin-like growth factor signaling (IIS) pathway acts as a ‘master signal’ that directs the development of either long-winged (LW) or short-winged (SW) morphs via regulation of the activity of Forkhead transcription factor subgroup O (NlFoxO). However, downstream effectors of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 52 publications
4
37
2
Order By: Relevance
“…Thus, wing morph variation in this species is an example of an environmentally induced polyphenism. The genetic basis of this polyphenism remains unknown, unlike studies on other environmentally induced wing polyphenisms where the IIS pathway is involved [14,15,37], our RNAi experiments demonstrate that knock down of genes in the IIS pathway do not alter induction of the different wing morphs. Thus, the nutrient-sensing IIS pathway is not ubiquitous in regulating insect wing polyphenism and our results therefore suggest that there are multiple genetic origins to how environmental cues are incorporated and result in wing polyphenism in insects.…”
Section: Discussioncontrasting
confidence: 58%
“…Thus, wing morph variation in this species is an example of an environmentally induced polyphenism. The genetic basis of this polyphenism remains unknown, unlike studies on other environmentally induced wing polyphenisms where the IIS pathway is involved [14,15,37], our RNAi experiments demonstrate that knock down of genes in the IIS pathway do not alter induction of the different wing morphs. Thus, the nutrient-sensing IIS pathway is not ubiquitous in regulating insect wing polyphenism and our results therefore suggest that there are multiple genetic origins to how environmental cues are incorporated and result in wing polyphenism in insects.…”
Section: Discussioncontrasting
confidence: 58%
“…To look into further how the LW phenotype developed in NlInR2 E4 mutants, we investigated wing-cell numbers in 5 th -instar nymphs by quantifying genomic DNA copy number using quantitative real-time PCR (qRT-PCR). Because wing buds grow explosively during an approximately 48 h time window at the beginning of the 5 th -instar nymph stage [ 48 ], fifth-instar nymphs were collected at 24 h intervals after ecdysis, and the wing buds were dissected from the second thoracic segment (T2W) and third thoracic segment (T3W) ( Fig 3A ). The number of cells in T2W from 5 th -intar NlInR2 E4 nymphs at 3 h after ecdysis (hAE) were comparable to that from Wt SW nymphs ( Fig 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that inactivation of NlFoxO resulted in a switch from SW to LW morphs in BPH [ 4 , 5 , 35 ]. To further explore the molecular basis regulated by Nl FoxO, transcriptomic profiles were conducted on LW- and SW-destined wing buds of 5th-instar nymphs, the wing-morph decisive stage of BPH [ 7 ]. We showed that knockdown of NlFoxO significantly altered the expression of 2128, 2902, and 1813 genes in forewing buds of 5th-instar nymphs at 24, 36, 48 hAE, respectively, and simultaneously altered the expression of 3466, 2533, and 2279 genes in hindwing buds.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies showed that the N. lugens FoxO homolog Nl FoxO relied on the insulin/insulin-like signaling (IIS) activity to direct wing buds developing into SW or LW morphs during the wing-morph decisive stage (the 5th-instar stage). High IIS activity inhibited Nl FoxO activity, leading to LW morphs, and vice versa [ 5 , 6 , 7 ]. However, the molecular basis by which Nl FoxO influences alternative wing morphs remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%